Programa de capacitação de estudantes de Psicologia para promoção do desenvolvimento de bebês de risco - Vital, Maria Lucia Naime Vidal (2008)
During the infant development, some risks are caused by internal and external conditions, with are dependent of the environment. Because of the lack of intervention in a troubled familiar environment or in a deficient institutional care, the babies at risk can show a damaged development. Brazilian daycare center privileges hygiene and primary care neglecting children education and their intervention. The present research intents to qualify students of Psychology College that wok with babies at risk to promote infantile development though play sessions. The collected data were extracted from intervention planning, reports and videos made during the execution of the play activities. The data referring to the babies were obtained through the application of the Operationalized Portage Inventory. The results will be compared with each individual performance during the intervention program, regarding to the students even the babies of the Inventory Portage.